PEMBUATAN SOFTWARE PENCATAT PENGUNJUNG PERPUSTAKAAN MENGGUNAKAN BARCODE DAN MYSQL BERBASIS BORLAND DELPHI 7.0 - Apriana, Apriana; Danusaputro, Hernowo (BERKALA FISIKA, 2009)
The library visitors counter system using barcode and MySQL based with Borland Delphi 7.0 has been done for ease in counting the visitors in a library and data to be displayed more accurate and comprehensive. Bar code which printed on visitors card is aimed at barcode scanner to read the code of the identity of visitors who will enter the library.Â At Borland Delphi 7.0 uses the pascal programming language that is integrated with the input of barcode and database MySQL able to display the time visitors enter the library. From this research it was found that Borland Delphi 7.0 software can read the records in the MySQL database and display properly on a monitor in accordance with the data stored on the visitors database. Â Keywords : library, barcode scanner, Borland Delphi 7.0, code barcode, MySQL